Political Regime Types and Income Inequality in Pakistan - Hamdard, Wasiq Ullah; Stanikzai, Irfan Ullah (MultiTech Publisher, 2024)
Rising income inequality is one of the major issues in the Pakistani economy. It has been investigated in different dimensions. Different cross-sectional and panel studies have extensively examined the connection between political regime types and income inequality over a specific period. The findings have displayed significant variations across countries and regions. This study delves into exploring the relationship between political regime types and income inequality, specifically in Pakistan, utilizing time series data spanning from 1972 to 2019. To measure political regime types, the Polity index is employed, while the Gini-Coefficient serves as the metric for income inequality. Additionally, this research takes into account various factors, such as GDP per capita, the ratio of direct taxes to GDP, the percentage of government expenditure on education relative to GDP, and the percentage of government expenditure on community and social services relative to GDP, in order to control for their direct effects. The stationarity of the data is assessed using the augmented Dickey-Fuller test, while the autoregressive distributive lag (ARDL) model is employed to examine the cointegrating relationship among the variables in the model. The empirical findings from the estimation affirm the presence of a lasting correlation between Pakistan's political regime types and wealth disparities. The findings show that different political regimes have a notable detrimental effect on the nation's economic disparity. To be more precise, a one percent increase in the Polity score is associated with a 0.45 percent long-term and a 0.25 percent short-term fall in the Gini Coefficient. This suggests that Pakistan should work toward a stable democratic political framework and put into place sustainable economic policies in order to successfully address income disparity and achieve a desirable level of income distribution